Jesus of the gospels, and Jesus of today - Budiselić, Ervin (Array, 2018)
Starting from the contemporary dominant values of tolerance, dialogue, and political correctness, this article analyses Jesus’ speech and teachings in the synoptic gospels in the light of these values. First, the article analyses Jesus’ speech about love, and then the focus is on Jesus’ harsh language and teaching. After that the article analyses reactions of different people and groups on his language and teaching. Based on this analysis, in the final section the article compares Jesus of the gospels with the distorted portray of Jesus that is sometimes present in contemporary Christianity. The conclusion that is made is that contemporary Western culture has distorted the image of Jesus from the gospels and has created modern Jesus which in his speech and teachings reflects today’s dominant values. However, Jesus is the same yesterday, today and forever, and we should be very careful to follow not some “contemporary Jesus,” but Jesus of the gospels.